Radiotherapy in Kimura's disease: A report of eight cases - Imjai Chitapanarux (2018)
Kimura's disease is a rare condition of chronic inflammatory disorder affecting the skin and subcutaneous tissue. It is predominantly in the head and neck region. The lesion is benign but may be persistent/recurrent and difficult to eradicate. Several forms of treatment have been used, including surgical excision, intralesional and oral corticosteroid, cryotherapy and radiotherapy. The authors report eight cases with histopathology consistent with Kimura's disease who received radiation therapy as a primary treatment or secondary treatment for recurrence after surgical excision in the Division of Therapeutic Radiology and Oncology, Chiang Mai University. The prescribed radiation doses varied from 30-40 Gy. With the mean follow-up time of 21 months, all eight patients were still free from disease at the time of analysis.